Gambaran Tingkat Pengetahuan Dan Perilaku Kepala Keluarga Tentang Pemberantasan Sarang Nyamuk Demam Berdarah Dengue Di Wilayah Kerja Puskesmas Kuta Selatan - I Made Dwi Sutakresna; Ni Made Marwati (Jurnal Kesehatan Lingkungan (JKL), 2020)
Indonesia which is a tropical country in general has a risk of contracting DHF. DHF attacks have broad implications for material and moral loss, work productivity and the most fatal is the loss of life. Badung regency is one of districts in Bali which is endemic area of DHF. According to data from Badung District Health Office in 2017, the number of DHF cases in 2017 was 941 cases with death rate 1 person (Incidence Rate: 146.2 per 100,000 population and CFR / death rate: 0.11%). The purpose of this research is to know description of head of household's knowledge and behavior on the eradication mosquito nest of dengue hemorrhagic fever in the working region of the Community Health Centre South Kuta. Type of research used is descriptive research. The sample size of this study was 96 Family Heads. The dominant male respondent characteristic is 67 people (70%), age is dominated by 46-60 years ie 52 people (54%) and high school education (51%). The result of this research is 96 people of head of household’s all have good knowledge level category about the eradication mosquito nest of dengue hemorrhagic fever. While the behavior of head of household’s about the eradication mosquito nest of dengue hemorrhagic fever got 14 people (14,6%) have enough behavioral category, while the rest as many as 82 people of head of household’s (85,4%) have good behavioral category. Keywords : The Eradication Mosquito Nest of Dengue Hemorrhagic Fever,                       Knowledge, Behavior, Head of Household's